Gender and generation: an intra-household analysis on access to resources in southern Mali - Groote, H.D.; N'golo Coulibaly, N. (1998)
This paper analyses the differences of access to productive resources within the household of southern Mali. Information was collected through separate group discussions with older men, younger men, and women from six villages. This information was complemented with a formal survey of 96 households in 12 villages. It was found that the essential differences between individuals related to access are gender, age, marriage and being the head of the household. The head of the household, always a man, manages the common fields, but otherwise men have less access than women to private plots and to the gathering of forest products. They have, however, more access to animals, and own all equipment. Differences between ethnic groups are very important. Methodologically, an effort has been made to reduce age into categories of generation and relation to the head of the household, but generally these variables did not perform very well. For future intra-household surveys following strata need to be distinguished for sampling: heads of household, dependent men and women. Other influential variables to be included in the survey are age, ethnic group, marriage and participation in field work.